Task-specific versus generalized mnemonic representations in parietal and prefrontal cortices - Sarma, Arup; Masse, Nicolas Y; Wang, Xiao-Jing; Freedman, David J (Nature neuroscience, 2016)
This study examines the effect of categorization-task training on parietal (PPC) and prefrontal (PFC) activity and finds a learning-dependent emergence of memory-related delay activity in PPC, whereas PFC shows delay-period selectivity both before and after categorization training. This reveals distinct roles of PFC and PPC in short-term working memory. Our ability to learn a wide range of behavioral tasks is essential for responding appropriately to sensory stimuli according to behavioral demands, but the underlying neural mechanism has been rarely examined by neurophysiological recordings in the same subjects across learning. To understand how learning new behavioral tasks affects neuronal representations, we recorded from posterior parietal cortex (PPC) before and after training on a visual motion categorization task. We found that categorization training influenced cognitive encoding in PPC, with a marked enhancement of memory-related delay-period encoding during the categorization task that was absent during a motion discrimination task before categorization training. In contrast, the prefrontal cortex (PFC) exhibited strong delay-period encoding during both discrimination and categorization tasks. This reveals a dissociation between PFC's and PPC's roles in working memory, with general engagement of PFC across multiple tasks, in contrast with more task-specific mnemonic encoding in PPC.